2020
DOI: 10.14393/bj-v36n4a2020-47738
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light and sucrose on photoautotrophic and photomixotrophic micropropagation of Physalis angulata

Abstract: The biotechnological interest in genus Physalis has increased in the last decades, however, there are still few micropropagation studies of this genus. The objective of this study was to evaluate P. angulata photoautotrophic and photomixotrophic micropropagation with gas exchange under seven light spectra and five concentrations of sucrose. Lighting were yellow, blue, white, red, green, red + blue LEDs and natural light filtered by mesh. Sucrose concentrations were 0, 7.5, 15, 22.5 and 30 g.L-1. Phytotechnical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Number of shoots per explant was highest under the R/B 20 and 0/M combination, which contrast with variables related to microstump growth and development which were highest under the FL 40 and 1/M combination. Some studies have shown that a light source with a broad light spectrum induces greater in vitro plant development (Batista et al 2018;Santos et al 2020;Miranda et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Number of shoots per explant was highest under the R/B 20 and 0/M combination, which contrast with variables related to microstump growth and development which were highest under the FL 40 and 1/M combination. Some studies have shown that a light source with a broad light spectrum induces greater in vitro plant development (Batista et al 2018;Santos et al 2020;Miranda et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The control of spectral quality, light intensity, and gas exchange during plant culture is essential to increase photosynthetic rates and shoot development R/B 40 µmol m -2 s -1 without a porous membrane. However, as a general rule it seems that membranes allowing gas exchange have a positive effect on in vitro propagation, likely to be associated to regular supply of CO 2 and O 2 , lower relative humidity and lower ethylene concentration inside the culture vessel (Hung et al 2016, Souza et al 2019Santos et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To simplify this process, this study divided the successive cluster seedlings of ginger into single plants, and the eld seedlings were directly established using photoautotrophic micropropagation technology. Photoautotrophic micropropagation helps the acclimatization phase, improving the anatomical and physiological characteristics that allow seedling survival and development (Santos et al 2020). The aim of this study was to develop a reliable and photoautotrophic micropropagation system that would improve the quality of ginger tissue culture seedlings and increase the survival rate during transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies report the advantage of using natural ventilation and forced ventilation with CO 2enrichment. For natural ventilation, studies with Pfaffia glomerata (Iarema et al, 2012;Saldanha et al, 2012;Corrêa et al, 2015a;Corrêa et al, 2015b), Capsicum annuum (Batista et al, 2017), Physalis angulata (Santos et al, 2020), Acca sellowiana (Caetano et al, 2021), Capsicum frutescens (Gris et al, 2021), Epidendrum fulgens (Fritsche;Pinheiro;Guerra, 2022), Guazuma ulmifolia (Jesus-Santana et al, 2022), for forced ventilation, studies with Pfaffia glomerata (Saldanha et al, 2013;Saldanha et al, 2014;Ferreira et al, 2019), Lippia alba (Batista et al, 2017), Etlingera elatior (Pinheiro et al, 2021), among others. These studies brought the benefits of the use of gas-porous membranes, which provides a reduction in relative humidity and ethylene gas inside the flasks, which can eliminate or drastically reduce morphophysiological disorders and increase survival during acclimatization.…”
Section: Introductionmentioning
confidence: 99%